Testing the Existence of January Effect in Indonesia and Kuala Lumpur Shariah Compliance - Helma Malini; Mohamad Jais (Jurnal Manajemen dan Bisnis Indonesia, 2014)
This paper investigates the existence of January Effect in Indonesia and Malaysia Shari’ah stock market and the implication for stock market efficiency. Shari’ah Compliance is relatively a new industry both for Indonesia and Malaysia, although the growth is continously increasing over the year. There are significant differences between investing in Shari’ah compliant than the conventional stock market, since Shari’ah capital market have to followed a set of rules form the stock exchange and also followed Islamic capital market law and principles. Study that focusing about Shari’ah compliance both for Indonesia and Malaysia is still rare, that is why this study taking one step further by examining the january effect in Indonesia and Malaysia Shariah compliance. Regression model with dummy variables and monthly price of companies that classified in the Indonesia and Malaysia Shari’ah compliance from January 2000 to December 2012 to test the Janaury effect in the stock return of Indonesia Shari’ah compliance and Kuala Lumpur Shari’ah compliance. It was empirically found that, although Janaury anomaly does not exist in Indonesia Shari’ah compliance and in Kuala Lumpur Shari’ah compliance. Other result showed that both Shari'ah compliance also enjoyed significant return in other month beside January which is July for Indonesia and September, October and November for Malaysia, which raises question against Efficient Market Hypothesis (EMH). Keywords: Calendar effects, Indonesia and Malaysia Shari’ah compliance, January Effect, Efficient Market Hypothesis